1988
DOI: 10.2214/ajr.151.2.317
|View full text |Cite
|
Sign up to set email alerts
|

The inability to detect kidney disease on the basis of echogenicity

Abstract: With the use of new sonographic technology, we have observed that the echogenicity of kidneys is often equal to that of the liver in patients in whom there is no evidence of renal disease; this observation conflicts with the generally accepted notion that a normal kidney is always less echogenic than the liver. In order to reassess renal echogenicity as an indicator of disease, three experienced radiologists blindly reviewed the sonograms of the right kidney and liver in 153 patients. The prevalence of renal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
1
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 0 publications
5
46
1
1
Order By: Relevance
“…For example, increased echogenicity was reported to have a 96% specificity (and 67% positive predictive value) for the presence of parenchymal kidney disease (3).…”
Section: Use Of Specific Parameters Obtained From Ultrasonography Andmentioning
confidence: 99%
“…For example, increased echogenicity was reported to have a 96% specificity (and 67% positive predictive value) for the presence of parenchymal kidney disease (3).…”
Section: Use Of Specific Parameters Obtained From Ultrasonography Andmentioning
confidence: 99%
“…Kidneys were considered abnormally echogenic if the echo intensity of the cortex of the right kidney was greater than that of adjacent liver. Kidneys with echogenicity equal to that of the adjacent liver were not included as abnormal because our earlier work has shown that this criteria of abnormality includes too many normal kidneys [7].…”
Section: The Resistive Index (Ri)mentioning
confidence: 99%
“…A limitation of this study was the subjectivity of the evaluation of the cortical echogenicity. Few reports have stated that densitometric measurement of echogenicity is more reliable than naked eye evaluations [10,12,13]. However, in our institute these measurements are not made in regular practice.…”
Section: Discussionmentioning
confidence: 83%
“…Because previous articles [3,5] have shown that in healthy pediatric subjects (neonates and infants excluded) echogenicity of the renal parenchyma is not increased, we believe that hyperechogenicity of renal parenchyma can be a nonspecific finding, a sign of (abdominal) illness varying from appendicitis to ileocecitis, infectious gastroenteritis or otherwise, rather than an indicator of renal disease. Only one study reported that renal echogenicity equal to the liver parenchyma is a nonspecific finding and does not suggest renal disease; that study, however, included only adults [10]. The cause of increased renal cortex echogenicity remains unclear.…”
Section: Discussionmentioning
confidence: 99%